Lessons Learned From VHA's Rapid Implementation of Virtual Whole Health Peer-Led Groups During the COVID-19 Pandemic: Staff Perspectives. (4th December 2022) - Anderson, Ekaterina; Dvorin, Kelly; Etingen, Bella; Barker, Anna M.; Rai, Zenith; Herbst, Abigail; Mozer, Reagan; Kingston, Rodger P.; Bokhour, Barbara
Background: Committed to implementing a person-centered, holistic (Whole Health) system of care, the Veterans Health Administration (VHA) developed a peer-led, group-based, multi-session "Taking Charge of My Life and Health" (TCMLH) program wherein Veterans reflect on values, set health and well-being-related goals, and provide mutual support. Prior work has demonstrated the positive impact of these groups. After face-to-face TCMLH groups were disrupted by the COVID-19 pandemic, VHA facilities rapidly implemented virtual (video-based) TCMLH groups. Objective: We sought to understand staff perspectives on the feasibility, challenges, and advantages of conducting TCMLH groups virtually. Methods: We completed semi-structured telephone interviews with 35 staff members involved in the implementation of virtual TCMLH groups across 12 VHA facilities and conducted rapid qualitative analysis of the interview transcripts. Results: Holding TCMLH groups virtually was viewed as feasible. Factors that promoted the implementation included use of standardized technology platforms amenable to delivery of group-based curriculum, availability of technical support, and adjustments in facilitator delivery style. The key drawbacks of the virtual format included difficulty maintaining engagement and barriers to relationship-building among participants. The perceived advantages of the virtual format included the positive influence of being in the home environment on Veterans' reflection, motivation, and self-disclosure, the greater convenience and accessibility of the virtual format, and the virtual group's role as an antidote to isolation during the COVID-19 pandemic. Conclusion: Faced with the disruption caused by the COVID-19 pandemic, VHA pivoted by rapidly implementing virtual TCMLH groups. Staff members involved in implementation noted that delivering TCMLH virtually was feasible and highlighted both challenges and advantages of the virtual format. A virtual group-based program in which participants set and pursue personally meaningful goals related to health and well-being in a supportive environment of their peers is a promising innovation that can be replicated in other health systems.